ШАХС ГЕНЕЗИСИДАГИ КОГНИТИВ РИВОЖЛАНИШИГА ДИНИЙ ЭЪТИҚОДНИ ТАЪСИРИ - Турсунов, Л.С. (SCIENCE and SOCIETY, 2024)
The role of religious faith is emphasized in the genesis of personality and its influence on the development of cognitive processes. In the process of personal development, attention is paid to the perfect mastery of the essence of "I" with the help of cognitive processes and faith.
Keywords: personality; belief; cognitive; genesis; role-playing; creative; descriptive; constructive; activity; simple work; speech; exhortation; desire; imagination; development